Comparison of activation patterns between masking and inattention tasks: a coordinate-based meta-analysis of implicit emotional face processing - Shi, Huqing; Wang, Xiang; Yao, Shuqiao (Frontiers in Human Neuroscience, 2013)
Neuroimaging studies of implicit emotional processing are important for understanding the neural mechanisms and its social and evolutionary significance. Two major experimental tasks are used to explore the mechanisms of implicit emotional processing: masking tasks and inattention tasks, both using emotional faces as stimuli. However, it is unclear whether they have identical or distinct neural substrates since few studies have compared the two tasks. The purpose of the present study was to explore the mechanisms of implicit processing of emotional faces, and compare the activation patterns between different tasks. Through a literature search, 41 studies exploring implicit processing of emotional faces were collected. A total of 830 healthy subjects and 513 foci were obtained. Separate activation likelihood estimation (ALE) meta-analyses were conducted for the entire group of studies and for different tasks for comparison purposes. The results showed that there were differences, as well as overlap, in activation patterns between masking and inattention tasks. Bilateral amygdala, middle occipital gyrus and fusiform gyrus were activated across both tasks. While masking tasks were more associated with inferior temporal gyrus, parahippocampal gyrus and amygdala, inattention tasks were more associated with right fusiform gyrus. The differences in activation patterns between masking and inattention tasks may be indicative of separate mechanisms underlying early and late stages of implicit emotional face processing.